2020
DOI: 10.3390/rs12172687
|View full text |Cite
|
Sign up to set email alerts
|

A Warming Mediterranean: 38 Years of Increasing Sea Surface Temperature

Abstract: The Mediterranean basin has been classified as a hot-spot for climate change. The Mediterranean Sea plays a fundamental regulatory role in the regional climate. We have analyzed the largest available and complete time series (1982–2019) of blended sea surface temperature (SST) data to study its seasonal cycle and look for a possible warming trend in the basin. From the analysis of the Mediterranean mean SST time series, a new temporal seasonal division is derived that differs from the one used in atmospheric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 40 publications
6
65
0
9
Order By: Relevance
“…This strong role of convective precipitation that gives place to heavy rainfalls and flash floods can be explained by the orography surrounding the Mediterranean Sea, the high frequency of surface lows (Romero et al, 1999;Jansà et al, 2014) and the strong potential instability in low levels favored by a warm sea. Pastor et al (2020) have found a continuous warming trend of 0,035ºC/y of SST for the entire Mediterranean, that means an accumulated change of 1,3ºC between 1982 and 2019, while Cramer et al (2018) have observed an increase of 1ºC for the entire Mediterranean Region and the same period. This differential trend between SST and air temperature near surface would be indicating a worsening of the thermodynamic conditions favorable to convection.…”
Section: Recent Changesmentioning
confidence: 94%
See 1 more Smart Citation
“…This strong role of convective precipitation that gives place to heavy rainfalls and flash floods can be explained by the orography surrounding the Mediterranean Sea, the high frequency of surface lows (Romero et al, 1999;Jansà et al, 2014) and the strong potential instability in low levels favored by a warm sea. Pastor et al (2020) have found a continuous warming trend of 0,035ºC/y of SST for the entire Mediterranean, that means an accumulated change of 1,3ºC between 1982 and 2019, while Cramer et al (2018) have observed an increase of 1ºC for the entire Mediterranean Region and the same period. This differential trend between SST and air temperature near surface would be indicating a worsening of the thermodynamic conditions favorable to convection.…”
Section: Recent Changesmentioning
confidence: 94%
“…The temperature of the Mediterranean Sea has increased by about 0.4ºC/decade between 1985 and 2006, increasing more in the East (about 0.5ºC/decade) than in the West (about 0.3ºC/decade). Recently, Pastor et al (2020) have showed that Sea Surface Temperature (SST) of the Mediterranean has increase 1.3ºC between 1982 and 2019. This warming is greatest in May, June and July.…”
Section: Main Environmental and Climate Changes In The Mediterranean mentioning
confidence: 99%
“…Resulta muy destacable que desde el año 2000 se han observado registros de 29-30ºC en el ecuador del verano en las aguas próximas a las Islas Baleares y Argelia. Esto último repercute sobre el clima de esta región: un mar más cálido favorece el incremento de las noches tropicales en la costa (Pastor et al, 2020). Esto se debe a que la temperatura del aire no puede descender al encontrarse una masa de agua tan cálida frente al litoral, mientras que por el día las brisas pueden contribuir a incrementar la sensación de bochorno, concretamente en días en que la temperatura del Mediterráneo alcanza o supera los 28ºC en la costa, porque el mar transmite el calor y la humedad al aire situado por encima de él.…”
Section: Aumento De La Temperatura Del Mar Mediterráneo Elemento Incentivador De La Intensidad De Las Lluvias Y De La Pérdida De Confort unclassified
“…Riesgos atmosféricos y cambio climático: propuestas didácticas para la región mediterránea en la enseñanza secundaria Figura 6. Incremento de la temperatura superficial marina del Mediterráneo Occidental Fuente: CEAM (2020) En el sector occidental de la cuenca mediterránea, los datos facilitados por Pastor et al (2020) muestran un calentamiento de 1,3 ºC entre 1982 y 2019. Este hecho repercute en que el calor acumulado en el Mediterráneo sea superior al propio calentamiento experimentado en el aire y registrado en los observatorios costeros.…”
Section: Aumento De La Temperatura Del Mar Mediterráneo Elemento Incentivador De La Intensidad De Las Lluvias Y De La Pérdida De Confort unclassified
See 1 more Smart Citation